Selection of pairs for intervarietal crossing of root chicory - O. M. Vyutnova; I. V. Smirnova; E. A. Evseeva; T. Yu. Polyanina; N. A. Ratnikova; I. A. Novikova (Овощи России, 2021)
Relevance. Modern agricultural production requires the creation of varieties that combine high productivity, quality, and adaptability. Taking into account the development trends of modern agriculture towards multiplicity, it is necessary to improve and expand the assortment, helping to meet the needs of both large and small producers of agricultural products. Due to the lack of material and human resources in the agricultural sector, there is a clear need for varieties and hybrids adapted to industrial cultivation and storage technologies. Existing zoned varieties of root chicory have a root crop length of 40 cm or more, and the soils of the area of cycoroseeding are mainly heavy in mechanical composition, where the use of digging devices to such a depth is impossible. Production requires varieties with a short root crop, which has the main mass concentrated in the upper part.Methods. The purpose of this work is to identify valuable genotypes in the soil and climate conditions of the non-Chernozem zone of the Russian Federation among the variety of varieties of chicory root of different ecological and geographical origin for use in the creation of the source material of selection by inter-port crosses.Results. When creating the source material for the selection of root chicory by the method of intervarietal crosses, one of the parents should choose local intrazonal varieties adapted to the soil and climatic conditions of the zone (Yaroslavsky, Gavrilov-Yamsky), and the second – off-zonal varieties with economically valuable qualities (short root crop, high yields and chemical-technological indicators, resistance to root rot) and donors of these traits (Kharpachi, Sleszka, BilogorkaOS-2, BilogorkaOS-3, Rexor, Wixor, Luxor).